Observation of Associated Near-Side and Away-Side Long-Range Correlations in √sNN=5.02 TeV Proton-Lead Collisions with the ATLAS Detector - Alonso, Francisco (2013)
Two-particle correlations in relative azimuthal angle (Δρ) and pseudorapidity (Δη) are measured in √sNN=5.02 TeV p+Pb collisions using the ATLAS detector at the LHC. The measurements are performed using approximately 1 μb-1 of data as a function of transverse momentum (pT) and the transverse energy (ΣETPb) summed over 3.1<η<4.9 in the direction of the Pb beam. The correlation function, constructed from charged particles, exhibits a long-range (2<|Δη|<5) "near-side" (Δρ∼0) correlation that grows rapidly with increasing ΣETPb. A long-range "away-side" (Δρ∼π) correlation, obtained by subtracting the expected contributions from recoiling dijets and other sources estimated using events with small ΣETPb, is found to match the near-side correlation in magnitude, shape (in Δη and Δρ) and ΣETPb dependence. The resultant Δρ correlation is approximately symmetric about π/2, and is consistent with a dominant cos2Δρ modulation for all ΣETPb ranges and particle pT.